Investigation of Phenolic, Flavonoid, Total Antioxidant Capacity, Vitamins, and Glutathione Contents of Aronia Melanocarpa (Michx.) Fruits - Servi, Refik; Karatas, Fikret; Özer, Dursun; Saydam, Sinan (My University, 2025)
The nutritional profile and antioxidant capacity of ripe aronia (Aronia melanocarpa) fruit were comprehensively analyzed using High-Performance Liquid Chromatography (HPLC) and Ultraviolet-visible (UV-vis) spectrophotometry. The content of fat-soluble vitamins was quantified as follows: vitamin A – 12.44 ± 0.69 µg/g, vitamin E – 19.51 ± 0.88 µg/g, ?-carotene – 51.64 ± 2.44 µg/g, and lycopene – 5.85 ± 0.30 µg/g. Water-soluble vitamins were also abundant, with ascorbic acid (vitamin C) being the most prevalent at 412.92 ± 12.61 µg/g, followed by riboflavin (16.43 ± 0.83 µg/g), pantothenic acid (36.37 ± 1.02 µg/g), and others including thiamine, nicotinic acid, pyridoxine, folic acid, and cyanocobalamin. Glutathione levels, essential for redox balance, were measured as 706.32 ± 19.46 µg/g for reduced glutathione (GSH) and 133.67 ± 8.28 µg/g for oxidized glutathione (GSSG). The fruit also exhibited high polyphenol and flavonoid contents, with total phenolics at 81.28 ± 3.21 µg gallic acid equivalents per gram and flavonoids at 65.55 ± 2.50 µg quercetin equivalents per gram. Antioxidant capacity was evaluated using two methods: the DPPH assay yielded an IC?? value of 23.17 ± 1.35 µg/mL, indicating strong radical scavenging activity, while the TEAC method demonstrated a total antioxidant capacity of 272.85 ± 10.91 µmol Trolox equivalents per gram. Ripe aronia fruit is rich in essential vitamins, glutathione, phenolic and flavonoid compounds, and possesses strong antioxidant capacity. These findings support its potential health benefits when consumed in appropriate amounts.
Keywords: Glutathione; Vitamins; Phenolic substance; Total antioxidant capacity; Aronia melanocarpa (Michx.); Flavonoid substance